‘Translation Archaeology’ in Practice: Researching the History of Buddhist Translation in Tibet - Raine, Roberta (Meta, 2014)
This paper is a report on a 10-month period of archival research aimed at uncovering key data related to the translation of the Indian Buddhist canon into Tibetan, a remarkable achievement that took some 900 years to complete. Our previous research relying on secondary (English-language) sources found that much information was either missing or unsubstantiated. In particular, the seemingly simple question of how many translators were involved in producing the Tibetan canon could not be satisfactorily answered. Without this foundational data, it is impossible to determine how many texts each translator produced, or who the most prolific translators were in Tibet’s history. Thus, Phase 1 of the archival research was to record the names, dates, and other relevant data of all the translators listed in the Tibetan canon. Phase 2 focused on researching biographical materials of some of the translators discovered during Phase 1. Pym calls this type of work “translation archaeology,” which is concerned with answering questions such as “who translated what, how, where, when, for whom and with what effect” (Pym 1998: 5). The data gathered at the end of the research period is presented and analyzed, difficulties encountered are discussed, and areas of further research are suggested.